Interoperability Challenges In Medical Record Management And Administration (Journal of Namibian Studies : History Politics Culture, 2022)
Interoperability in medical record management is crucial for seamless data exchange and communication between disparate healthcare systems. However, achieving interoperability poses significant challenges in healthcare administration. This paper examines the key challenges hindering interoperability, including fragmented systems, lack of data standardization, security concerns, technical barriers, organizational obstacles, and regulatory complexities. Potential solutions such as adopting common data standards, interoperability frameworks, and collaborative governance practices are discussed. By addressing these challenges, healthcare stakeholders can enhance interoperability, leading to improved healthcare quality and patient outcomes.